Consumer Network Evolution Game Based on Product Crowdfunding - Xiaodong Qian, Yao Lu (Forest Chemicals Review)
Recently, with the continuous innovation of Internet finance, the model of crowdsourcing emerged, in order to make the product crowdsourcing program obtain more consumer support, promote the success of crowdsourcing and achieve the efficient development of the crowdsourcing industry, this paper took the consumer group as the research object, and then analyzed the evolution of Crowdfunding consumers cooperation in the context of product crowdsourcing. According to the public goods game model, a two strategy multi person evolution game system for crowdsourced consumers based on replication dynamics was established, the integrated influencing factors considering node distance and node importance were introduced, the strategy selection mechanism of the traditional replication dynamics model was optimized, and mutations are introduced, and the effects of mutation factors on the evolutionary stability equilibrium were analyzed. Research found: (1) both support and no support for crowdsourcing are evolutionarily stable strategies in the context of traditional replication dynamics. (2) In the context of improved dynamics, no supporting and partially favoring crowdsourcing are evolutionarily stable strategies, and the presence of a mutation somewhat inhibits the success of crowdsourcing. At the same time, in order to promote the success of crowdsourcing programs, managers should enhance product impact and effectively motivate consumers to engage in product crowdsourcing by means of directed marketing; On the other hand, consumers mutations should be reduced or even avoided as much as possible, improving product quality and increasing consumer loyalty.